Telementoring in Leg Fasciotomies via Mixed-Reality: Clinical Evaluation of the STAR Platform. (19th February 2020) - Rojas-Muñoz, Edgar; Cabrera, Maria Eugenia; Lin, Chengyuan; Sánchez-Tamayo, Natalia; Andersen, Dan; Popescu, Voicu; Anderson, Kathryn; Zarzaur, Ben; Mullis, Brian; Wachs, Juan P
ABSTRACT: Introduction: Point-of-injury (POI) care requires immediate specialized assistance but delays and expertise lapses can lead to complications. In such scenarios, telementoring can benefit health practitioners by transmitting guidance from remote specialists. However, current telementoring systems are not appropriate for POI care. This article clinically evaluates our System for Telementoring with Augmented Reality (STAR), a novel telementoring system based on an augmented reality head-mounted display. The system is portable, self-contained, and displays virtual surgical guidance onto the operating field. These capabilities can facilitate telementoring in POI scenarios while mitigating limitations of conventional telementoring systems. Methods: Twenty participants performed leg fasciotomies on cadaveric specimens under either one of two experimental conditions: telementoring using STAR; or without telementoring but reviewing the procedure beforehand. An expert surgeon evaluated the participants' performance in terms of completion time, number of errors, and procedure-related scores. Additional metrics included a self-reported confidence score and postexperiment questionnaires. Results: STAR effectively delivered surgical guidance to nonspecialist health practitioners: participants using STAR performed fewer errors and obtained higher procedure-related scores. Conclusions: This work validates STAR as a viable surgical telementoring platform, which could be further explored to aid in scenarios where life-saving care must be delivered in a prehospital setting.